The position of custom ('Urf/'Adat) in issuing fatwa: in the works of Ibn 'Abidin al-Shami (d. 1252/1836) - Ali, Mohammed Farid (Dar al-Wahi Publication, 2018)
Fatwa issued currently by Shari'ah scholars, committees, and muftis occasionally fall short of meeting the challenges of modern society. Ibn 'Abidin’s concept of custom (‘urf) and its application provide a basic guide to meet the modern challenges in its totality. The present work refers to his three works—Sharh 'Uqud Rasm al-Mufti, Nashr al-'urf fi bina ba'd al-ahkam 'ala al-'urf, and Radd al-Muhtar 'ala al-Durr al-Mukhtar Sharh Tanwir al-Absar (al-Ḥashiyah)—written in 13th century A.H. These works present 'urf as a practical instrument for muftis and those responsible to issue fatwa. The first work is used as an overall framework, while the other two works offer commentaries on the latter, providing details and cases of application. This work enunciates that Ibn 'Abidin identifies custom as effective in Islamic law only if it fulfills the condition to specify the legal text (takhsis al-nass), without opposing it completely. The variations of 'urf in society will only affect those legal issues that are custom-related and not directly based on nass (Qur’an and Sunnah). Moreover, all custom-related issues in manifest rulings (zahir al-riwayah) of a Legal School are subjected to change as custom changes.